2019
DOI: 10.11648/j.earth.20190801.14
|View full text |Cite
|
Sign up to set email alerts
|

Geophagic Clayey Materials of Sabga Locality (North West Cameroon): Genesis and Medical Interest

Abstract: Geophagia, the deliberate ingestion of clayey materials, is a complex eating behaviour with obscure etiology and numerous health/medical problems. Geological, mineralogical and geochemical studies were carried out on Sabga geophagic clayey materials located within a trachyte Bamenda mountain, about 16 km east of Bamenda town (North West Cameroon), in order to define the genesis, and its medical interest. Four (04) samples were characterized by different techniques: description of outcrops and pits, particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It is difficult to assess the proper dosage of the different components in geophagic materials; as a result, it is easy to consume excessive quantities of valuable minerals as well as dangerously large amounts of harmful or toxic materials, resulting in electrolyte imbalances and toxicity (Chamy et al, 2022). For example, one of the consequences of lead exposure, which has been found in some geophagic clay, is intelligence decline in exposed children, while in adults it can cause cancer over time (Kalguem et al, 2019;Olajide-Kayode et al, 2023). Another element of interest is zinc (Zn), which is generally considered non-toxic, but exposure to high concentrations can cause detrimental health effects such as growth retardation in infants, abdominal pain, diarrhea, and electrolyte imbalance (Ncube et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to assess the proper dosage of the different components in geophagic materials; as a result, it is easy to consume excessive quantities of valuable minerals as well as dangerously large amounts of harmful or toxic materials, resulting in electrolyte imbalances and toxicity (Chamy et al, 2022). For example, one of the consequences of lead exposure, which has been found in some geophagic clay, is intelligence decline in exposed children, while in adults it can cause cancer over time (Kalguem et al, 2019;Olajide-Kayode et al, 2023). Another element of interest is zinc (Zn), which is generally considered non-toxic, but exposure to high concentrations can cause detrimental health effects such as growth retardation in infants, abdominal pain, diarrhea, and electrolyte imbalance (Ncube et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out on geophagic clays in Cameroon [13,[26][27][28][29][30][31][32][33]. In 2002, the European Commission alerted the Cameroonian Ministry of Public Health [27] about abnormally high amount of lead (100 times higher than the maximum permissible level) in geophagic kaolin carried from Cameroon to Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the study by Frazzoli et al [27] indicated that geophagic clays sold in markets in Cameroon contained high concentrations of lead, cadmium and mercury. Kenne Kalguem et al [32] also noted that geophagic clays from Sabga (Northwest Cameroon) contain high radioactive (Th, U), carcinogenic (Cr, Cu, Pb, Ni) and teratogenic (Cu, Zn, Pb) elements. Frazzoli et al [27] recommended that provenance studies of geophagic clays in Cameroon be carried out to establish environmental characteristics of these clays.…”
Section: Introductionmentioning
confidence: 99%